2017
DOI: 10.1177/2053434517744071
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive home-based care coordination for vulnerable elders with dementia: Maximizing Independence at Home-Plus—Study protocol

Abstract: Introduction Despite availability of effective care strategies for dementia, most health care systems are not yet organized or equipped to provide comprehensive family-centered dementia care management. Maximizing Independence at Home-Plus is a promising new model of dementia care coordination being tested in the U.S. through a Health Care Innovation Award funded by the Centers for Medicare and Medicaid Services that may serve as a model to address these delivery gaps, improve outcomes, and lower costs. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…See Table S1, published as supplementary material online attached to the electronic version of this paper, for a comparison of MIND-HCIA and MIND-RCT study designs and methods. Further protocol details are described elsewhere (Samus et al, 2017;Samus et al, 2018). Both studies were approved by the Johns Hopkins Medicine Institutional Review Board (IRB).…”
Section: Methodsmentioning
confidence: 99%
“…See Table S1, published as supplementary material online attached to the electronic version of this paper, for a comparison of MIND-HCIA and MIND-RCT study designs and methods. Further protocol details are described elsewhere (Samus et al, 2017;Samus et al, 2018). Both studies were approved by the Johns Hopkins Medicine Institutional Review Board (IRB).…”
Section: Methodsmentioning
confidence: 99%
“…Older adults with ADRD tend to be clinically complex; roughly half have three or more chronic conditions ( Lin et al, 2013 ). They are at elevated risk for avoidable hospitalizations for chronic conditions, hospital readmission, urinary tract infection, sepsis, and other adverse outcomes ( Daiello et al, 2014 ; Lin et al, 2013 ; LinNeumann, 2017; Shen et al, 2012 ), which may be preventable with timely care and effective care ( Amjad et al, 2018 ; Bellantonio et al, 2008 ; Naylor et al, 2014 ; Samus et al, 2014 , 2015 , 2017 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that 18 months of care coordination through individualized care planning, implementation of a care plan, monitoring and reassessment had beneficial effects on the time to transition from home, number of dementiarelated unmet needs, quality of life (QoL) and, importantly, a potentially clinically relevant reduction in selfreported number of hours spent on caregiving tasks, as a measure of caregiver burden [14,15]. Developing this model further, the MIND at Home-Plus study included an additional 340 persons to evaluate the effect on longterm care placement, hospitalization and health-care expenditures of a 24-month homecare coordination program for PWD [16]. The MIND at Home-Streamlined trial is now refining the intervention to investigate its impact on time to long-term care placement, needs, burdens and QoL in PWDs and their caregivers, as well as cost utilization [17].…”
Section: Rationale For the Present Trialmentioning
confidence: 99%